2015
DOI: 10.1002/ejoc.201501426
|View full text |Cite
|
Sign up to set email alerts
|

Introverted Phosphorus‐Au Cavitands for Catalytic Use

Abstract: A preparative synthesis of an inwardly directed phosphoramidite-Au complex is described and a description of some of its catalytic performance. The molecular structure was determined by crystallographic analysis, which disclosed that the phosphoramidite ligand points "out" and places the complexed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…[16] In seeking to develop a reactivity profile for 2, we followed the examples that we had previously explored for 1. [9] In examining the 2-mediated Conia-ene [17] reaction we were surprised to find no evidence of cyclization -instead, bis-Au cavitand 2 brought two alkynes together to result in a dimerization event (Scheme 2). The resulting enyne was isolated as the major product in 45 % yield.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…[16] In seeking to develop a reactivity profile for 2, we followed the examples that we had previously explored for 1. [9] In examining the 2-mediated Conia-ene [17] reaction we were surprised to find no evidence of cyclization -instead, bis-Au cavitand 2 brought two alkynes together to result in a dimerization event (Scheme 2). The resulting enyne was isolated as the major product in 45 % yield.…”
Section: Resultsmentioning
confidence: 98%
“…We again conducted thorough control experiments: (1) utilizing the mono-gold complex [9] shown in panel (a) of Scheme 1, (2) using commercially available AuCl·PPh 3 , (3) using phosphorus-free AuCl·S(CH 3 ) 2 , and (4) using the gold-free host 1. Dimers were not observed in any case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iwasawa and co‐workers developed a resorcin[4]arene‐based cavitand, containing a phosphorous atom that can function as a ligand that coordinates to a metal center . The lone pair of the P atom is oriented toward the cavity space, so a coordinating metal ion is directed into the cavity .…”
Section: Covalently Functionalized Catalystsmentioning
confidence: 99%
“…This strategy was previously described by Rebek and co‐workers using palladium, and coordination complexes with rhodium and platinum have been reported as well. Iwasawa and co‐workers attached a gold center to the resorcin[4]arene cavitand (Figure ) . The crystal structure showed that the gold center pointed inward and was surrounded by the walls of the cavity.…”
Section: Covalently Functionalized Catalystsmentioning
confidence: 99%